Evaluation of biochemical and antioxidant dynamics during the co‐fermentation of dehusked barley with Rhizopus oryzae and Lactobacillus plantarum. Issue 2 (5th December 2019) - Wang, Kun; Niu, Mengmeng; Song, Dawei; Liu, Yang; Wu, Yue; Zhao, Jing; Li, Shize; Lu, Baoxin
Abstract: Barley is an ancient and important functional crop. In this study, the biochemical and antioxidant dynamics of dehusked barley during co‐fermentation with Lactobacillus plantarum and Rhizopus oryzae were investigated. Results showed that amino acid nitrogen, soluble protein, <10 kDa peptide, and free phenolic contents increased with fermentation time; whereas the lactic acid bacteria count, reducing sugar, and free flavonoid contents showed a tendency to increase first and then decrease. SDS‐PAGE analysis indicated that bands at >25 and <18.4 kDa were shown with improved intensity with time, whereas bands at 18.4–25 kDa were disappeared. Additionally, fermentation time led to an increase in DPPH, hydroxyl, ABTS + radical scavenging activity, and ferric reducing antioxidant power. Thus, this study demonstrated that co‐fermentation with L. plantarum and R. oryzae could improve nutrition and potential bioactivity of barley, and use barley as a good solid‐state food carrier for probiotics. Practical applications: Barley is rich in nutrition and has a huge production. However, due to its high‐fiber and special protein composition, there is a certain palatability problem whether it is used to produce flour or other products. Therefore, most of the barley is destined to animal feed and malt, and only a small part is used directly for human consumption. Aiming at this problem, on the basis of the optimization of the fermentation process at early stage, our results further demonstrated co‐fermentation with L. plantarum and R. oryzae could enhance the nutritional value and potential bioactivity of barley, thus providing a novel approach to develop functional barley food and improve the direct utilization rate of barley in food processing. Abstract : Amino acid nitrogen, soluble protein, <10 kDa peptide, and free phenolic contents in dehusked barley increased with the fermentation time. Co‐fermentation with Lactobacillus plantarum and Rhizopus oryzae improved the antioxidant activity of dehusked barley. Dehusked barley could be used as a good solid‐state food carrier for probiotics.